Commercial Use of Satellite Remote Sensing Data and Civil Liability - Young-Ju Kim (Laws)
This paper explores the civil liability issues arising from the commercial use of satellite remote sensing data, a rapidly growing sector in the space industry. With the increasing reliance on satellite data for various applications, such as agriculture, disaster response, and climate monitoring, legal challenges have emerged, particularly concerning the accuracy and commercialization of satellite data. The study examines the concept and characteristics of satellite remote sensing, focusing on the legal relationships between data providers, users, and third parties. It analyzes the legal framework regulating this business across different jurisdictions, including the United States, Canada, Germany, France, and Japan. Key issues addressed include liability for inaccurate data, licensing agreements, and the rights and obligations of parties involved in satellite data transactions. Through this analysis, the paper offers legal and institutional recommendations to support the development and stability of the commercial satellite data industry, contributing to the establishment of a comprehensive legal framework for the space sector.